The relationship between teacher anxiety and self-efficacy among pre-service teachers at the Kulliyyah of Education, IIUM - Jebur, Hammood Msayer (Kulliyyah of Education, International Islamic University Malaysia, 2016)
This present research was conducted with three main objectives, namely to explore the prevalence of teacher anxiety and self-efficacy among pre-service teachers of English, Arabic and Islamic Education at the Kulliyyah of Education, International Islamic University Malaysia; identify the predictors of teacher anxiety and self-efficacy from among five demographic factors, i.e. namely age, gender, year of study, major and programme (school orientation or teaching practicum experience); and find out whether there is a significant relationship between teacher anxiety and self-efficacy. A total of 199 undergraduate students from the three majors participated in the survey. A 41-item questionnaire was employed to measure students' teacher anxiety and self-efficacy. The items were pilot-tested before being administered to the respondents. The data were analysed quantitatively using descriptive statistics, multiple regression and Pearson correlation coefficient. The outcomes showed that teacher anxiety was prevalent among the respondents. Compared to teacher anxiety, self-efficacy was less prevalent, although many reported being confident in the three self-efficacy sub-constructs assessed in the study, i.e. instructional strategies, classroom management, and student engagement. Major is the strongest predictor of self-efficacy among the respondents, and there is a relationship between two dimensions of teacher anxiety with all the constructs of self-efficacy. Overall, the results indicate no linear relationship between those factors. The results showed that age was the strongest predictor of teacher anxiety among the respondents, followed by major and program. Gender and year of study, however, were not found to be statistically significant predictors either anxiety or efficacy. No significant relationship was observed between teacher anxiety and self-efficacy. The results would benefit all those involved in teacher preparation programmes, particularly the pre-service teachers themselves, as well as lecturers, supervisors, mentors, school principals, school students, and the Ministry of Education Malaysia.